Longitudinal patterns in benthic communities in an urban stream under restoration - Tanya J. Blakely; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2005)
Okeover Stream, on the University of Canterbury campus in Christchurch, New Zealand, has been the subject of restoration efforts since 1998. Our study focused on quantifying the response of this urban stream to current restoration efforts. Initially, physico‐chemical conditions and biological communities at three sites along the Okeover Stream were compared with three physically similar sites on each of nearby Waimairi Stream and Avon River. General physical and chemical parameters were similar in all streams with circum‐neutral pH, specific conductivity ranging from 167 to 173 μS/cm, dissolved oxygen ranging from 9.0 to 9.2 mg/litre, low turbidity, and similar hydrological conditions. However, analysis of heavy metals in the sediment showed mean lead (Pb) concentrations in Okeover and Waimairi Streams exceeded ANZECC ISQG‐low trigger values (86.9 and 83.7 mg/kg, respectively), whereas Avon River sediment Pb levels (27.3 mg/ kg) were below trigger values. Benthic taxonomic richness did not differ significantly among the three streams. However, Okeover Stream community was dominated by the amphipod Paracalliopefluviatilis, whereas in Waimairi Stream and Avon River the gastropod snails Potamopyrgus antipodarum and Physella acuta were the dominant benthic fauna. A further assessment made at six sites along 1200 m of Okeover Stream showed no distinct longitudinal patterns in physical or chemical conditions, but there was a strong pattern in benthic macroinvertebrate communities. Taxonomic richness and caddisfly diversity increased downstream, with twice as many taxa at the most downstream site than the uppermost sampling site. In upper reaches, copper (Cu), Pb, and zinc (Zn) concentrations in sediments all exceeded ANZECC ISQG‐low trigger values. Despite ongoing restoration efforts in Okeover Stream, sedimentation, the presence of high heavy metal concentrations, intermittent flows in headwaters, and possible barriers to adult recolonisation seem to be having a continuing negative impact on benthic communities, especially in the headwaters.